Pengembangan Kelompok PKK Sebagai Agen Penggerak Ketahanan Pangan Keluarga di Desa Petani - Setiawati Setiawati; Efni Ramli; Khairiah Khairiah (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The Family Welfare Empowerment Group (PKK) Petani village, as a driving force for food security was often underdeveloped. The purpose of this community service was to improve the knowledge and skills of PKK members in food diversification, balanced nutrition, and productive yard cultivation techniques; Encourage optimal used of household yards as a sustainable source of family food; strengthen the institutional capacity of the Family Welfare Movement (PKK) and increase public awareness of the importance of food security and balanced nutrition at the family level. The research problem formulation was to determine how to develop the PKK Group as a Driving Agent for Family Food Security in Farmer Villages. The service to society implementation method be carried out through a participatory approach. Data collection techniques through interviews. Based on the interviews, it was found that PKK groups in farmer villages had implemented various education and empowerment programs, but their success and impact had not been evenly distributed. Existing programs tend to be incidental and unsustainable. Significant challenges remain, such as a lack of physical facilities (land and seeds), capacity (training and coaching), and adequate financial support. Although PKK had a strong foundation because most of its members were farmers, long-term success depended heavily on strong external support, especially from the government, in the form of funding, facilities, and price stability to strengthen food security optimally and sustainably.